Enhancement of gratitude in the context of elite athletes: outcomes and challenges. Issue 5 (19th October 2020) - Howells, Kerry; Fitzallen, Noleine
ABSTRACT: Gratitude has been heralded as important to emotional, social and societal wellbeing. A burgeoning body of recent research on the positive impact of gratitude in sport calls for an investigation into its relevance to the field of elite sport, particularly for building resilience and enhancing relationships. An interpretivist/constructivist research approach was adopted to explore the practices, outcomes and challenges of gratitude of 10 Australian elite athletes – Olympians and Para-Olympians – who participated in a workshop on gratitude. Sports represented in this cohort included cycling, sailing, track and field, beach volleyball and diving. Semi-structured interviews were used to generate data, which were explored using content analysis. Enhancement of gratitude with the elite athletes resulted in the adoption of more meaningful and authentic gratitude towards others. Positive impact of gratitude expressed in this way was reported in the areas of improved attitude; greater awareness; better capacity to deal with stress; increased confidence to express gratitude; and enhanced performance. The paper also discusses the perceived challenges of expressing gratitude within this context.